COFFEE SHOP DI KOTA PEKANBARU (KAJIAN KASUS) - Tiarafica Rizki Friorita; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Urban community is a modern society. A developing urban society always creating an innovation as a city facilty. Coffee shop is a facilty which created by a new change caused by life style in city, its context was different from an usual coffee shop dan only found in cities. As a city facility, coffee shop can be enjoyed by anyone from any commnunity in a city, starting those from high class, middle class, and even still affordable by low class community. Because of this different context of a coffee shop made a coffee shop worth to be enjoyed by people of the cities, basically this kind of coffee shop sell different services, from facility, atmosphere, and extraordinary product from an ordinary coffee shop. Because of the nature of urban community, they tend to have an open mind so they would like to try new things and new people, primarily in coffee shop. The increasingly growth phenomenon of Coffee Shop in Pekanbaru city is the purpose of this research. Theory used in this research is urban growth and modernizations theory. In this research, there are six sources, those who become source for this research are customers who enjoy coffee shop facilities which basically grouped as coffee lovers and people who only following the trends of coffee shop. Research data mining in this research are done by interviews, observation, and documentation. Interviews done in this research are structured interviews where researcher prepared an interview handbook. According to past research, it can be concluded that in Pekanbaru city, customs of visiting coffee shop made this activity as daily routines such as visiting every day even more than once or twice a day to release fatigue from daily activity in the city, this is innovation from new lifestyle of grwoing urban society.Keywords: coffee shop,lifestyle.